Bens-App (Benson relaxation Application) for Reducing Side Effects of Chemotherapy among Breast Cancer Patients: Development and Usability Study - Dewi Irawaty; Muhamad Adam; Hendra (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: Chemotherapy's effects decrease the quality of life in breast cancer patients. Smartphone apps are ready to deliver Benson's relaxation program. Objective: This study aimed to develop and assess the usefulness of the “Bens-App (Benson’s relaxation application)” for breast cancer patients. Methods: The study included 28 breast cancer patients in Baladhika Husada Hospital in Jember. Indonesia. Developed the application in several stages (1) literature review to determine the content, (2) the application feasibility test carried out by 2 experts in medical surgical nursing and oncology. Performed usability tests after the patient had used Bens-App for 7 days. The mHealth App Usability Questionnaire (MAUQ) was used to measure usability. Results: Bens-App contains 6 features (1) health information about breast cancer, Benson's relaxation, and fatigue (2) Benson's relaxation guide using audio (3) "reminder" reminds patients to perform Benson relaxation twice/day (4) self-monitoring which in graphical form on the home page, (5) documentation via the web to observe patient activity with the Bens-App. Usability tests results show 3 items get the highest average MAUQ score, "I will use this application again" (6.5/7), "Applications that are useful for health and me" (6.5/7), "Applications improve my access to health services" (6.5/7) and the lowest average score on the item" I can use the application when the internet network is poor or unavailable” (5.28/7). Conclusion; Bens-App can be received well, although some items still need improvement. Further research in larger populations is required